Development of a Income Statement for UMKM CleanShoes Surabaya - Tony Soebijono; Martinus Sony Eristiawan (CONTABILITA : Journal of Accounting and Finance, 2025)
This study focuses on the development of an income statement for CleanShoes Surabaya, a micro, small, and medium enterprise (MSME) specializing in shoe cleaning services. The primary objective is to implement a standardized financial reporting system in alignment with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) to enhance financial transparency and decision-making processes. By adopting the cash basis accounting method, the income statement accurately reflects the company's financial performance over a specific period. The methodology involves collecting financial data from CleanShoes Surabaya, including revenues from regular and premium shoe cleaning services, and expenses such as cleaning materials, employee wages, utilities, rent, depreciation, and marketing costs. The data is then structured into an income statement format as prescribed by SAK EMKM. The findings indicate that the standardized income statement provides a clear overview of the company's profitability, enabling the management to make informed financial decisions and strategize for sustainable growth. This approach also ensures compliance with financial reporting standards, which is crucial for building stakeholder trust and accessing potential funding opportunities.